The Meaning of Relationships Without Status for Generation Z: A Phenomenological Study in Cirebon City - Isma Azza; Siti Khumayah; Farida Nurfalah (Indonesian Journal Publisher, 2026)
Advances in digital technology and social media have transformed how Generation Z interacts, contributing to the emergence of Relationships Without Status, a romantic relationship characterized by emotional intimacy without formal commitment. This study aims to explore the meaning of Relationships Without Status among Generation Z in Cirebon, identify the emotional and social challenges they experience, and examine the influence of the local socio-cultural environment. A qualitative phenomenological approach was employed using in-depth interviews with five informants, supported by non-participant observation, documentation, and a literature review. Data were analyzed through transcript coding, data reduction, thematic interpretation, and narrative presentation. The findings indicate that Relationships Without Status provide emotional freedom and opportunities for self-discovery but also generate anxiety, uncertainty, overthinking, and social pressure due to the absence of commitment. In Cirebon, where religious and traditional values remain influential, these relationships reflect a negotiation between modern relationship practices and prevailing social norms, highlighting both emotional flexibility and psychological vulnerability among Generation Z.